(3GdLhGgQ GdeVjI aj WHbGJ GdMfajIs - (3YHO GdbGOQ Hf eMeO Hf fUQGddg, GdeYQha HGHf CHj GdhaGA GdbQTj GdJejej GdeUQj,J (B775 (3g` s ((3eMeO Hf eMeO Hf eMeO s)
(3ChdgG (B:s
(3GdMeO hGdYXeI hGdcHQjGA def dg GdCSeGA GdMSfi s
(3BNQgG (B:s
(3hGJHYhG QVhGf Gddg hGddg Ph aVd YXje, SHMGf QHc QH GdYRI YeG jUahf hSdGe Ydi GdoeQSdjf hGdMeO ddg QH GdYGdejf s
(3GfXQ Qbe (B207 (3JGQjNs
(3fSNI KGfjI GdfGSN gh SHW GdfhjQjs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B42s
Keywords: (3GdJGQjNs